The Mobile Phone Addiction and Depression Among High School Students: The Roles of Cyberbullying Victimization, Perpetration, and Gender - Wu, Wenzhi; Chen, Yongchuan; Shi, Xiuying; Lv, Hua; Bai, Rui; Guo, Zhichao; Yu, Lei; Liu, Yilin; Liu, Jianping; Chen, Yatang; Zeng, Yong (Frontiers in Psychology, 2022)
Objective: To examine the relation between mobile phone addiction and high school students’ depression, and its inner mechanism—the sequential mediating roles of the cyberbullying victimization and the cyberbullying perpetration in this relationship. Methods: 1297 high school students were recruited to complete the Smartphone Addiction Scale, European Cyberbullying Intervention Project Questionnaire and The Center for Epidemiological Studies Depression Scale. Results: (1) mobile phone addiction was positively correlated with and high school students’ depression; (2) cyberbullying victimization and the cyberbullying perpetration significantly mediated the relation between mobile phone addiction and high school students’ depression, which contained tow mediating paths—the independent mediating effects of cyberbullying victimization and the sequential mediating effect of cyberbullying victimization and the cyberbullying perpetration. (3) there are gender differences in the sequential mediation model, and boys who are victims of cyberbullying are more likely to develop into cyberbullying perpetrators than girls. Conclusion: The results of this study indicate that depression among high school students with mobile phone addiction can be eliminated through the development of cyberbullying victimization and the cyberbullying perpetration.